2021
DOI: 10.3892/ol.2021.12825
|View full text |Cite
|
Sign up to set email alerts
|

LZTR1: A promising adaptor of the CUL3 family (Review)

Abstract: The study of the disorders of ubiquitin-mediated proteasomal degradation may unravel the molecular basis of human diseases, such as cancer (prostate cancer, lung cancer and liver cancer, etc.) and nervous system disease (Parkinson's disease, Alzheimer's disease and Huntington's disease, etc.) and help in the design of new therapeutic methods. Leucine zipper-like transcription regulator 1 (LZTR1) is an important substrate recognition subunit of cullin-RING E3 ligase that plays an important role in the regulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 125 publications
(172 reference statements)
0
11
0
Order By: Relevance
“…The association of the locus spanning the LZTR1 gene is also notable as this gene encodes an important leucine-zipper transcriptional regulator that is linked to cell proliferation in cancer [ 33 ]. The lead variant at the locus, rs112544, has a significant and broad impact on the expression of the THAP7 gene and its antisense transcript, THAP7-AS1 .…”
Section: Discussionmentioning
confidence: 99%
“…The association of the locus spanning the LZTR1 gene is also notable as this gene encodes an important leucine-zipper transcriptional regulator that is linked to cell proliferation in cancer [ 33 ]. The lead variant at the locus, rs112544, has a significant and broad impact on the expression of the THAP7 gene and its antisense transcript, THAP7-AS1 .…”
Section: Discussionmentioning
confidence: 99%
“…The dysregulation of UPS is usually caused by the mutations of E3 ubiquitin ligase, such as SPOP (8,157) and leucine zipper-like transcription regulator 1 (LZTR1) (158). The mutations of SPOP and LZTR1 occur mostly in domains bound to the substrate, severely affecting their ability to bind to substrates, inhibiting the ubiquitination and degradation of substrates, and leading to the accumulation of substrates (4,6,159). Notably, although one study showed the lack of somatic mutation in the coding sequence of Siah1 (55), the mutations of Siah1 are rarely reported.…”
Section: Discussionmentioning
confidence: 99%
“…The LZTR1 protein is an adaptor for Cullin 3 ubiquitin ligase (LZTR1‐CUL3 complex), which is implicated in the polubiquitination and degradation of the RAS‐family proteins (Zhang et al, 2021). LZTR1 includes six Kelch motifs at the N‐terminus (KT‐I‐VI), which are involved in the substrates recruitment, and two C‐terminal BTB‐BACK domains (BTB‐I‐II), which bind Cullin 3 (Steklov et al, 2018).…”
Section: Figurementioning
confidence: 99%
“…These data suggest that both predicted amino acid changes could alter the free energy of the protein by affecting its stability; a fact that may compromise the formation of the LZTR1‐CUL3 complex. Accordingly, the abrogation of LZTR1‐CUL3 complex has been reported as the main effect of disease‐associated LZTR1 causative variants (Zhang et al, 2021).…”
Section: Figurementioning
confidence: 99%